Methodology for Developing Creativity in the Teaching and Learning Process of Differential and Integral Calculus - Sánchez Companioni, Wilfredo (2025)
This article discusses the development of student creativity through the teaching-learning process and aims to propose a methodology focused on a professional approach to content, to foster creativity in students pursuing an Accounting and Finance degree through the teaching-learning process of Differential and Integral Calculus. The research was guided by a mixed approach, facilitating both theoretical and practical analysis from quantitative and qualitative perspectives. This required the use of theoretical, empirical, and statistical-mathematical methods to delve deeper into the subject. Document analysis, product review of the activities, observation, and interviews were used to gather information on the level of creativity development among the 12 students participating in the study. The results were then interpreted using descriptive statistics and qualitatively assessed. The main outcome of this research is a methodology, which includes procedures, methodological guidelines for its implementation, and examples illustrating its practical use. Its evaluation, based on expert feedback, yielded positive opinions regarding its quality and practical applicability. Therefore, its adaptation to other topics within the course and the design of new teaching tasks is recommended.